2020
DOI: 10.1038/s41598-020-69794-2
|View full text |Cite
|
Sign up to set email alerts
|

There is a U shaped association between non high density lipoprotein cholesterol with overall and cardiovascular mortality in chronic kidney disease stage 3–5

Abstract: Hsuan chiu 1 , pei-Yu Wu 2,3,4 , Jiun-chi Huang 2,3,4 , Hung-pin tu 5 , Ming-Yen Lin 2 , Szu-chia chen 2,3,4,6* & Jer-Ming chang 2,4 Dyslipidemia is common in patients with chronic kidney disease (cKD), however the relationship between dyslipidemia and mortality in patients with moderate to severe cKD remains controversial. non-high-density lipoprotein (HDL) cholesterol has been reported to be a more accurate predictor of clinical outcomes than conventional lipid measurements. Hence, the aim of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 56 publications
6
17
0
1
Order By: Relevance
“…We also observed that lower non-HDL-C linked to higher mortality risk in hypertensive population. Consistent with our results, Chiu et al also found the U-shaped association in chronic kidney disease patients; the lowest mortality risk was observed at non-HDL-C levels of 116.2–143.9 mg/dl, and non-HDL-C <116.2 mg/dl appeared with higher mortality ( 27 ). Non-HDL-C was inversely associated with mortality among hemodialysis patients in the analysis of Chang et al ( 24 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also observed that lower non-HDL-C linked to higher mortality risk in hypertensive population. Consistent with our results, Chiu et al also found the U-shaped association in chronic kidney disease patients; the lowest mortality risk was observed at non-HDL-C levels of 116.2–143.9 mg/dl, and non-HDL-C <116.2 mg/dl appeared with higher mortality ( 27 ). Non-HDL-C was inversely associated with mortality among hemodialysis patients in the analysis of Chang et al ( 24 ).…”
Section: Discussionsupporting
confidence: 91%
“…Similar inverse associations were also found in elderly ( 25 , 26 ). Recently, a U-shaped relationship was also discovered ( 27 ). In hypertensive population, rising non-HDL-C could develop arterial stiffness ( 28 , 29 ) and even accelerate the process of hypertension ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among patients with CKD, however, this relationship is much less obvious. Low total and LDL-C levels were also associated with higher mortality in patients with moderate to advanced stages of CKD, who were not yet on dialysis (33). The inverse association between low total and LDL-C levels and mortality may be explained in part by the presence of the so-called malnutrition-inflammation syndrome (32).…”
Section: Discussionmentioning
confidence: 99%
“…Lower total and LDL cholesterol are markers of protein-energy wasting in CKD patients and were shown to be associated with increased death risk in hemodialysis patients, but the results in CKD patients were conflicting [17]. In a newer study by Chiu et al [18], a U-shaped relationship between non-high-density lipoprotein cholesterol and the risk of overall and cardiovascular mortality in patients with CKD stage 3–5 was established. Interestingly, we found no significant difference in hemoglobin between the groups; however, in multivariate Cox regression analysis, hemoglobin reached borderline significance for cardiovascular mortality, and it was a significant predictor of all-cause mortality.…”
Section: Disscussionmentioning
confidence: 99%